Comparative Examinations of Structural Responses of Concrete Reinforced with Treated Oil Palm Empty Fruit Bunch (TOPEFB) and Untreated Oil Palm Empty Fruit Bunch (OPEFB) Fibres - Christopher Fapohunda; H. B. Adekunle; H. O. Adebayo; V. O. Olapade; A. J. Kilani (Electronic Journal of Structural Engineering, 2023)
The findings from the investigation conducted, to compare the structural performance of concrete containing treated (TOPEFB) and untreated Empty Oil Palm Fruit Bunch (OPEFB) fibres are presented in this paper. For the TOPEFB fibres, the dried fibres were treated with 0.2% NAOH solution following the procedures of appropriate authority. The structural parameters investigated were consistencies, setting times, densities, compressive and tensile strengths of concrete incorporating TOPEFB and OPEFB fibres in the mix. The addition of fibres was limited to 1.20% by weight of cement in the concrete. The interval of addition was 0.2%. The results showed that (i) the setting times of mortars containing TOPEFB fibres were higher than that of mortars with OPEFB fibres, (ii) concrete specimens containing TOPEFB fibres are more workable that concrete specimens with OPEFB fibres, (iii) densities of concrete specimens containing OPEFB fibres were in the range for normal concrete applications while the densities for specimens with TOPEFB developed densities that fell in the heavy weight concrete classification, (iv) concrete specimens containing TOPEFB fibres developed higher compressive strengths than specimens with OPEFB fibres and (v) tensile strengths of concrete specimens containing TOPEFB fibres were higher than specimens with OPEFB fibres by at least 59.04%. The overall conclusion from the findings of this study is that concrete specimens containing TOPEFB fibres have superior structural properties than specimens with OPEFB fibres